Standalone cages versus plate-augmented fusion in multilevel anterior cervical discectomy and fusion: A 12-month prospective study balancing clinical equivalence and radiological superiority - Sayed Mohamed Elgoyoushi (Journal of Craniovertebral Junction and Spine)
Purpose: Anterior cervical discectomy and fusion (ACDF) is a gold standard treatment for multilevel degenerative cervical pathology, yet controversy persists regarding the necessity of anterior cervical plates (ACPs) in modern cage-based constructs. This prospective study compares the clinical and radiological outcomes of standalone cages versus plate-augmented systems in multilevel ACDF, addressing critical debates on biomechanical stability versus procedural simplicity. Materials and Methods: A prospective cohort of 100 patients undergoing multilevel ACDF (2+ levels) was equally divided into two groups: standalone cages (Group I, n = 50) and cages with ACP (Group II, n = 50). Clinical outcomes (Visual Analog Scale [VAS] for neck/arm pain and Neck Disability Index [NDI]) and radiological parameters (fusion rates and cervical lordosis) were assessed preoperatively and at 6/12 months postoperatively. Complications including dysphagia, pseudoarthrosis, and C5 palsy were systematically recorded. Results: Both the groups demonstrated significant improvements in VAS (neck: 7.2→2.1 vs. 7.0→1.9; arm: 6.8→1.8 vs. 6.5→1.7) and NDI (48%→18% vs. 50%→16%) at 12 months (P > 0.05). Radiologically, Group II exhibited superior outcomes: (1) fusion rates: 94% versus 82% (P = 0.03) and (2) lordosis maintenance: 12.5° versus 9.8° (P = 0.01). Complication rates were comparable (dysphagia: 8% vs. 10%; pseudoarthrosis: 6% vs. 4%; P > 0.05). Conclusion: While standalone cages achieve comparable short-term symptom relief, plate augmentation offers superior radiological stability in multilevel ACDF, preserving alignment and optimizing fusion success without increasing perioperative risks. These findings support selective plate use in complex, multilevel constructs while affirming standalone cages as a viable option for patients with contraindications to plating. This study refines evidence-based decision-making in cervical spine surgery, balancing innovation with biomechanical rigor.